Hyperandrogenism stimulates inflammation and promote apoptosis of cumulus cells - Xu, F.; Liu, R.; Cao, X. (Cellular and Molecular Biology, 2017)
To explore roles of androgen and cytokines such as IL-1, IL-6 and TNF-Î± in PCOS. Cumulus cells were isolated from rat COCs and divided into two sets of experiments. Set 1 includes 4 groups: Control group, IL-1 group (final concentration at 5 nM), IL-6 group (final concentration at 5nM) and TNF-Î± group (final concentration at 5nM). Set 2 also include 4 groups: Control group, Androgen group 1 (final concentration at 1 nM), Androgen group 2 (final concentration at 10 nM) and Androgen group 3 (final concentration at 100 nM). Androgen, at final concentration of 100 nM, can induce secretion of cytokines include IL-1, IL-6 and TNF-Î± in cumulus cells. This in turn leads to cell apoptosis probably through ROS production as well as promotes oocyte maturation. Androgen and cytokines that developed during PCOS contribute to ROS production, apoptosis and oocyte maturation in that disease.